IMPLEMENTASI TEKNIS: TRANSFORMASI KEAMANAN DIGITAL SEKOLAH MELALUI PENDEKATAN DEFENSE-IN-DEPTH DAN ZERO-TRUST - Feny Rita Fiantika; Prastyo, Danang; Dian Kusmaharti; Wahyu Susiloningsih (Kanigara, 2026)
Digital transformation in the education sector has accelerated the adoption of cloud-based services, Learning Management Systems (LMS), mobile devices, and digital school management platforms, while simultaneously increasing cybersecurity risks. Many schools still face challenges in implementing effective cybersecurity governance, including weak user authentication, irregular system updates, limited cybersecurity awareness, and the absence of formal incident response procedures. This community service program aimed to strengthen schools' cybersecurity capacity through the implementation of Defense-in-Depth and Zero Trust Architecture approaches. The program employed initial observation, needs assessment, technical training, implementation assistance, phishing simulation, evaluation, and continuous monitoring involving school principals, teachers, school administrators, and information technology personnel. The implementation resulted in the development of school digital security policies, deployment of Multi-Factor Authentication (MFA) for priority accounts, establishment of weekly Patch Management procedures, implementation of Endpoint Protection, introduction of Mobile Device Management (MDM), and preparation of an Incident Response Plan (IRP). Furthermore, participants demonstrated improved cybersecurity awareness and digital security literacy. The integration of Defense-in-Depth and Zero Trust approaches enhanced organizational cyber resilience through identity management, access control, endpoint protection, and continuous security monitoring. This program provides a practical and sustainable cybersecurity implementation model that can support secure digital transformation in educational institutions.